PERSEPSI KONSULTAN PAJAK DAN FISKUS TERHADAP IMPLEMENTASI CORE TAX ADMINISTRATION SYSTEM (CTAS) DI KOTA SURAKARTA - Paquita Vernanda Pudji Asmoro; Antin Okfitasari; Erna Chotidjah Suhatmi; Pravasanti, Yuwita Ariessa (ITB AAS Indonesia Surakarta, 2025)
This study aims to analyze the perceptions of tax consultants and tax authorities towards the implementation of the Core Tax Administration System (CTAS) in Surakarta City. CTAS is a digital taxation system developed by the Directorate General of Taxes to unify all tax administration processes in one platform. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, documentation, and online questionnaires (Google Form). The results of the study indicate that both tax consultants and tax authorities view CTAS as an important innovation in increasing efficiency and transparency. However, the implementation of this system is considered still not optimal due to limited human resource readiness and technical constraints. These findings recommend the need for increased socialization, technical training, and strengthening of system infrastructure.